The Extract of Bellucia pentamera Naudin Leaves as Bioherbicide of The Chromolaena odorata (L.) R.M.King & H.Rob. Germination and Growth - Lidia Gusvita Nasra; Solfiyeni; Chairul (Universitas Nusa Bangsa, 2023)
Threats that can cause loss of biodiversity include the presence of invasive foreign plants. One of these invasive plants is from the Melastomataceae family with the species Bellucia pentamera Naudin, and this species can trigger a decline in ecosystem diversity. B. pentamera contains a chemical compound that can be used as an herbicide, phenolic, and flavonoid compounds, which can retard the growth of other plants that surround them like noxious weeds. Bioherbicides need to be used as an environmentally friendly alternative drug control method to overcome and reduce their adverse effects. This research was carried out to determine the impact and concentration of administering B. pentamera leaf extract on the germination and growth of Chromolaena odorata. The study used experimental methods with a completely randomized design (CRD) with six variations consisting of treatment of 0, 10, 15, 20, 25, and 30% with a four-time repetition. The research results showed the effect of giving greater concentrations of B. pentamera leaf extract, causing the germination and growth of C. odorata to be increasingly hampered. Providing extracts with concentrations of 20% and 25% are effective for inhibiting the germination and growth of C. odorata.